Improved Electrogeometric Model of UHV Transmission Line Based on Long Gap Discharge and Its Application - Hu, Yuanchao; Yang, Minghao; Qu, Lu; An, Yunzhu; Wang, Jing; Cheng, Yan; Sha, Xiao; Wang, Qingchen; Ma, Chenghui; An, Bingchen; Chen, Dan (Frontiers in Energy Research, 2022)
Based on long air gap discharge test data and lightning return stroke observation data, an improved electrogeometric model (EGM) considering terrain conditions is established and verified to analyze the lightning shielding performance of UHV transmission lines. The striking distance formula is modified as rs = 0.13 (I2 + 40I)0.814. In this paper, the lightning shielding failure rate of three-phase conductors of EHV and UHV transmission lines calculated by the improved EGM model is consistent with the lightning observation data of actual transmission lines in Japan and the scaled lightning discharge simulation experimental results of UHV transmission lines in plains and mountainous areas of China, which verifies the applicability of the improved EGM model to evaluate the lightning shielding performance of large-scale UHV transmission lines. The improved EGM model is applied to evaluate the influence of tower type and slope steepness on the shielding failure tripping rate of UHV transmission lines. The shielding failure tripping rate of the SZ322 tower is higher than that of the SZT1 tower, and the shielding failure tripping rate of UHV transmission lines is greatly affected by slope gradient and increases with the increase of slope gradient.